Programmed cell death - Jiang, Xuejun (Henry Stewart Talks, 2021)
Programmed vs. regulated cell death, Morphological features of apoptosis, The function and activation of caspases, Evolutionary conservation of cell death, The role of mitochondria in cell death, Apoptosis and its role in cancer development, Other cell death modalities